The Role of International Pisa Research in Enhancing Mathematical Literacy in Students (Eurasian Journal of History, Geography and Economics, 2022)
The article describes the issue of control of knowledge on the basis of the International Assessment Program PISA and on its basis the provision of assessment assignments to students and young people within the framework of science.